Replication Rate, Framing, and Format Affect Attitudes and Decisions about Science Claims - Barnes, Ralph M.; Tobin, Stephanie J.; Johnston, Heather M.; MacKenzie, Noah; Taglang, Chelsea M. (Frontiers in Psychology, 2016)
A series of five experiments examined how the evaluation of a scientific finding was influenced by information about the number of studies that had successfully replicated the initial finding. The experiments also tested the impact of frame (negative, positive) and numeric format (percentage, natural frequency) on the evaluation of scientific findings. In Experiments 1 through 4, an attitude difference score served as the dependent measure, while a measure of choice served as the dependent measure in Experiment 5. Results from a diverse sample of 188 non-institutionalized U.S. adults (Experiment 2) and 730 undergraduate college students (Experiments 1, 3, and 4) indicated that attitudes became more positive as the replication rate increased and attitudes were more positive when the replication information was framed positively. The results also indicate that the manner in which replication rate was framed had a greater impact on attitude than the replication rate itself. The large effect for frame was attenuated somewhat when information about replication was presented in the form of natural frequencies rather than percentages. A fifth study employing 662 undergraduate college students in a task in which choice served as the dependent measure confirmed the framing effect and replicated the replication rate effect in the positive frame condition, but provided no evidence that the use of natural frequencies diminished the effect.